Cognitive fitness modulates gender differences in sleep and mental health among competitive athletes under chronic stress - Mascaro, Luis; Drummond, Sean P. A.; Leota, Josh; Boardman, Johanna M.; Hoffman, Daniel; Rajaratnam, Shantha M. W.; Aidman, Eugene; Facer-Childs, Elise R. (Frontiers in Physiology, 2023)
Objectives: Mental fitness is increasingly considered a key component of an athlete’s competitive arsenal. Active domains of mental fitness include cognitive fitness, sleep, and mental health; and these domains can differ between men and women athletes. Our study investigated the associations of cognitive fitness and gender to sleep and mental health, and the interaction between cognitive fitness and gender on sleep and mental health, in competitive athletes during the COVID-19 pandemic. Methods: 82 athletes competing at levels from regional/state to international (49% women, M-age = 23.3 years) completed measures of self-control, intolerance of uncertainty, and impulsivity (together representing constructs of cognitive fitness), items about sleep (total sleep time, sleep latency, and mid-sleep time on free days) and a measure of mental health (depression, anxiety, and stress). Results: Women athletes reported lower self-control, higher intolerance of uncertainty, and higher positive urgency impulsivity compared with men athletes. Women reported sleeping later, but this gender difference disappeared after controlling for cognitive fitness. Women athletes – after controlling for cognitive fitness – reported higher depression, anxiety, and stress. Across genders, higher self-control was associated with lower depression, and lower intolerance of uncertainty was associated with lower anxiety. Higher sensation seeking was associated with lower depression and stress, and higher premeditation was associated with greater total sleep time and anxiety. Higher perseverance was associated with higher depression for men – but not women – athletes. Conclusion: Women athletes in our sample reported poorer cognitive fitness and mental health compared to men athletes. Most cognitive fitness factors protected competitive athletes under chronic stress, but some exposed them to poorer mental health. Future work should examine the sources of gender differences. Our findings suggest a need to develop tailored interventions aimed at improving athlete well-being, with a particular focus on women athletes.